Effects of Powdered Rosa canina L (Subspecies Lito) Containing Seeds and Shells to Improve Cell Longevity and Wrinkles and Elasticity of the Skin - L. Phetcharat; K. Wongsuphasawat; K. Winther (Disease and Health Research: New Insights Vol. 2, 2024)
Background: The longevity of cell membranes is essential to avoid changes related to aging. Photoaging damages collagen, elastin, and the skin’s moisture barrier, leading to wrinkles, sagging, toughening, and dry skin texture. Rose hips, the red fleshy berries of the dog rose (Rosa canina), have been known to have medicinal properties since the time of Pliny the Elder (23–79 BC). Objective: The primary objective of this study is to evaluate the effects of a rose hip powder (Hyben Vital®) made from seeds and shells of subspecies Lito, on cell senescence, skin wrinkling, and aging. Methods: A total of 34 healthy subjects, aged 35–65 years, with wrinkles on the face (crow’s- feet) were subjected to a randomized and double-blinded clinical study of the effects of the rose hip powder, as compared to astaxanthin, a well-known remedy against wrinkles. During the 8-week study, half of the participants ingested the standardized rose hip product, while the other half ingested astaxanthin. Objective measurements of facial wrinkles, skin moisture, and elasticity were made by using Visioscan, Corneometer, and Cutometer at the beginning of the study, after 4 weeks, and after 8 weeks. Evaluation of participant satisfaction with both supplements was assessed using questionnaires. In addition, the effect of the rose hip preparation on cell longevity was measured in terms of leakage of hemoglobin through red cell membranes (hemolytic index) in blood samples kept in a blood bank for 5 weeks. In the comparative study of the effects of rose hip vs astaxanthin on the facial skin, the magnitude of changes over time (i.e., baseline to 4–8 weeks) for the same patient were analyzed by one-way analysis of variance (ANOVA). The significance of all values was attained with P#0.05. Results: In the double-blinded study, the rose hip group showed statistically significant improvements in crow’s-feet wrinkles (P,0.05), skin moisture (P,0.05), and elasticity (P,0.05) after 8 weeks of treatment. A similar improvement was observed for astaxanthin, with P-values 0.05, 0.001, and 0.05. Likewise, both groups expressed equal satisfaction with the results obtained in their self-assessments. The rose hip powder further resulted in increased cell longevity of erythrocyte cells during storage for 5 weeks in a blood bank. Comparing the effectiveness between the two treatments, there was no significant difference in the skin improvement effect between rose hip powder and the well-known antiwrinkle and antiphotoaging remedy astaxanthin. Conclusion: Results suggest that intake of the standardized rose hip powder (Hyben Vital®) improves aging-induced skin conditions. The apparent stabilizing effects of the rose hip product on cell membranes of stored erythrocyte cells observed in this study may contribute to improving cell longevity and obstructing skin aging.